Emerging blaNDM-positive Salmonella enterica in Chinese pediatric infections - Yefang Ke; Zhe Zhu; Wenbo Lu; Wenyuan Liu; Lina Ye; Chenghao Jia; Min Yue (Microbiology Spectrum)
ABSTRACT Non-typhoidal Salmonella (NTS) is a common zoonotic foodborne pathogen, whose rising antimicrobial resistance has been an urgent threat to global public health. Here, we reported two carbapenem-resistant Salmonella enterica (CRSE) strains (NBFE-049 and NBFE-164) carrying the blaNDM genes, which were recovered from two Chinese children, belonged to Salmonella enterica serovar Typhimurium (S. Typhimurium) monophasic variant (S. 1,4,[5],12:i:-) ST34 (a sequence type) and S. Typhimurium ST19, respectively. Genes blaNDM-5 and blaNDM-13 were detected in NBFE-049 and NBFE-164, respectively. The blaNDM-5 in NBFE-049 was located in an IncHI2-type plasmid, named pNBFE-049. In NBFE-164, the blaNDM-13 was located in an IncI1-type plasmid, named pNBFE-164. The plasmid pNBFE-164 successfully transferred its resistance phenotype into the recipient strain Escherichia coli J53 with a high efficiency of 1.1 × 10−2, while no transconjugants were obtained in pNBFE-049 conjugation assays. We further elucidated the genetic relationships of globally occurring New Delhi Metallo-β-lactamase (NDM)-positive strains and locally distributed clinical strains within the same serovar. The closest relative of NBFE-049 was clinical Salmonella strain 1722, which was recovered in 2020 and differed by only three Single Nucleotide Polymorphisms (SNPs). No NDM-positive ST19 could be found in the National Center for Biotechnology Information (NCBI) database, and NBFE-164 showed a close genetic relationship with the other ST19 in this area. To sum up, we suggested the potential contributions of clonal spread and plasmid-mediated blaNDM transfer in CRSE dissemination. This study reported the complete genome of two blaNDM-carrying S. Typhimurium isolates, shedding new insights into the antimicrobial resistance mechanisms and dissemination patterns of the emerging CRSE.IMPORTANCENTS is one of the most common zoonotic pathogens that causes foodborne illnesses, while S. Typhimurium is one of the most common serovars. With the rising prevalence of multi-resistant Salmonella worldwide, carbapenems have emerged as the last-line antibiotics for treating severe bacterial infections. In this study, we reported the genomic characteristics of two carbapenem-resistant S. Typhimurium strains, which were recovered from two pediatric patients, carrying blaNDM-5 and blaNDM-13, providing new insights into the antimicrobial resistance deteriminants and transmission risk of blaNDM-positive NTS in China. We suggested the potential contributions of clonal spread and plasmid-mediated blaNDM transfer in CRSE dissemination. Future enhanced surveillance policy should mitigate CRSE spreading, and more importantly, clinical antimicrobial therapeutic regimens should be adjusted accordingly.